The Manuscript and How to Deal with it - bin Yahya, Ibtisam Salim; Ihbil, Mohammed Abdul Majeed (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
Manuscripts are the great wealth that our nation possesses, and it needs to be revived again, in order to contribute to spreading life in the nation, and also the manuscript is considered as a container in which the opinions of authors scholars are preserved in any scientific issue, and thus highlights its importance in knowing the events and developments witnessed in the issues that the manuscript deals with. The topic aims to preserve the manuscripts and how to deal with them and how to achieve them. The research was divided into an introduction, a preface, and three topics, each topic according to its axes or branches, and a conclusion, followed by a list proving the sources and references.